BOOK REVIEW: Zachary J. Goldberg, Evil Matters: A Philosophical Inquiry, 2021, New York: Routledge Studies in Ethics and Moral Theory, 254 pages, ISBN: 978-0-367-89402-3 (hbk); ISBN: 978-1-032-05242-7 (pbk); ISBN: 978-1-003-02157-5 (ebk) - SAIDI, Amira Rihab (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
Zachary J. Goldberg is a Ph.D. holder in moral philosophy from Arizona State University. For the present moment, he is an Ethics Innovation Manager at Trilateral Research, a UK and IE- ethical AI software-based enterprise. His research interests are applied ethics and moral, political, and social philosophy. In this landmark study, Evil Matters: A Philosophical Inquiry, Zachary Goldberg presents the findings of his long-term research project entitled Components of Evil: An Analysis of Secular Moral Evil and its Normative and Societal Implications at Ludwig-Maximilians-Universität, Munich. Distant from any religious contextualization of the concept of evil, Goldberg, in this volume, delivers a complete study on evil action by revisiting previous philosophical studies on evil acts and their relation to human understanding. The context of this volume focuses solely on evil performative actions and does not discuss evil personhood.